Pengaruh Kepemimpinan Dan Work Life Balance , Terhadap Kinerja Pegawai Melalui Produktivitas Kerja Sebagai Variabel Intervening Pada Sekretariat Daerah Kabupaten Padang Pariaman - Resha Aulia Putri; Hilda Mary; Nia Nadilla (CV. ITTC INDONESIA, 2026)
This study aims to analyze and examine the influence of Leadership and Work-Life Balance on Employee Performance through Work Productivity as an intervening variable at the Regional Secretariat of Padang Pariaman Regency. This research employed a quantitative approach using a survey method. The population consisted of all employees of the Regional Secretariat of Padang Pariaman Regency, with a total sample of 108 respondents obtained through a saturated sampling technique. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3.0 software. The results indicate that Leadership has a positive and significant effect on Work Productivity. Work-Life Balance also has a positive and significant effect on Work Productivity. Furthermore, Leadership and Work-Life Balance each have a positive and significant effect on Employee Performance. Work Productivity has a positive and significant effect on Employee Performance. Additionally, Work Productivity successfully mediates the relationship between Leadership and Work-Life Balance on Employee Performance. The R-Square value shows that the contribution of Leadership and Work-Life Balance to Work Productivity is 0.818 or 81.8%, while their contribution to Employee Performance is 0.762 or 76.2%. This study implies that improving leadership quality and implementing an effective work-life balance can enhance work productivity, which ultimately improves employee performance within the Regional Secretariat of Padang Pariaman Regency.